2015
DOI: 10.1007/s13213-015-1113-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of the part of the bacterial community associated with field-grown tall fescue (Festuca arundinacea) cv. SFRO Don Tomás in Uruguay

Abstract: The aims of this study were to isolate, characterize and identify the native culturable putative endophytic bacterial community associated with tall fescue (Festuca arundinacea) cv. SFRO Don Tomás, cultivated in Uruguay, and to study the effects of inoculation on cv. SFRO Don Tomás and the commercial cv. Tacuabé. A total of 342 isolates were collected from surface-sterilized roots, stems and seeds of healthy cv. SFRO Don Tomás. The functional ability of the isolates to produce indole, to solubilize minerals (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…These bacteria may be rhizospheric, epiphytic, endophytic or a combination of all of these (Turner et al, 2013). Regardless of their location, molecular genetic studies of the culturable and increasingly the non-culturable, diversity of diazotrophs associated with the aforementioned non-legumes has shown that it is enormous (Ueda et al, 1995;Engelhard et al, 2000;Burbano et al, 2011;Thaweenut et al, 2011;Fischer et al, 2012;Taul e et al, 2012;Videira et al, 2012Videira et al, , 2013Sessitsch et al, 2012;De los Santos et al, 2016). Of particular interest is the endophytic population of diazotrophs, since it was suggested that their oxygenrestricted niche within the tissues of host plants allows them to more efficiently fix N 2 , but also to exchange the fixed N-containing products (ammonium) for carboncontaining compounds (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…These bacteria may be rhizospheric, epiphytic, endophytic or a combination of all of these (Turner et al, 2013). Regardless of their location, molecular genetic studies of the culturable and increasingly the non-culturable, diversity of diazotrophs associated with the aforementioned non-legumes has shown that it is enormous (Ueda et al, 1995;Engelhard et al, 2000;Burbano et al, 2011;Thaweenut et al, 2011;Fischer et al, 2012;Taul e et al, 2012;Videira et al, 2012Videira et al, , 2013Sessitsch et al, 2012;De los Santos et al, 2016). Of particular interest is the endophytic population of diazotrophs, since it was suggested that their oxygenrestricted niche within the tissues of host plants allows them to more efficiently fix N 2 , but also to exchange the fixed N-containing products (ammonium) for carboncontaining compounds (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In the purified components, soil isolates of S. sampsonii can produce heptaene polyene antibiotics [18,27], In addition, S. sampsonii has been shown to produce hydrolytic enzymes, such as amylase, chitinase, protease, and lipase [19]. Studies at the molecular level have focused on strain identification and the phylogenesis of related species [28][29][30][31][32][33][34][35]. The complete genome sequence of Streptomyces sampsonii KJ40 was recently described by our lab [36], resulting in the discovery of a large number of gene encoding chitinases and enzymes involved in secondary metabolite production.…”
mentioning
confidence: 99%
“…Curtobacterium is a Gram-positive endophytic bacterial genus in rice seeds (Oryza sativa), field-grown tall fescue (L. arundinacea) and Noccaea goesingensis (De Los Santos et al, 2015;Mano et al, 2006;Ruiz et al, 2011). Some Curtobacterium strains provide host growth promotion and pathogen antagonistic effects (De Los Santos et al, 2015;Ruiz et al, 2011). Paenibacillus was the only genus from phylum Firmicutes in both LM and HM seeds (LM 3%, HM 4%).…”
Section: Discussion a Complex Bacterial Community Associated With Turmentioning
confidence: 99%